Simple Additive Weighting untuk Front-end Framework Terbaik - Yusuf, Lestari; Hidayatulloh, Taufik; Nurlaela, Dini; Utami, Lila Dini; Hasan, Fuad Nur (Teknik Informatika Fakultas Ilmu Komputer Univeristas Muslim Indonesia, 2020)
Web applications that used to run on a desktop in recent years have received huge demand for this area to be more sophisticated and complex, not only that, but users also want web applications to run on mobile devices. Web appearance that is only designed for computer devices will make users difficult when opening a web page display on a different device. By using the CSS framework library, web developers will be greatly helped in making the program more responsive and can also be run on a variety of Open Source both Windows, iOS, and Android. Decision-making system that can determine the best front-end Framework can be an alternative solution for web developers to determine which front-end framework is easier and more convenient to use. Simple Additive Weighting is used to analyze and decide which the best alternative with calculations that take five main criteria in this research that is Preprocessor, Responsive, Browser Support, Easy to Use, and Template. In this study the highest prefects were obtained by Bootstrap 1,000 while for foundation and bulma get a large prefensie s 0.868 and 0.820.